The Phosphatase PHLPP2 Plays a Key Role in the Regulation of Pancreatic Beta-Cell Survival. (3rd January 2020) - Hribal, Marta Letizia; Mancuso, Elettra; Arcidiacono, Gaetano Paride; Greco, Annalisa; Musca, Donatella; Procopio, Teresa; Ruffo, Mariafrancesca; Sesti, Giorgio
Abstract : Currently available antidiabetic treatments fail to halt, and may even exacerbate, pancreatic β -cell exhaustion, a key feature of type 2 diabetes pathogenesis; thus, strategies to prevent, or reverse, β -cell failure should be actively sought. The serine threonine kinase Akt has a key role in the regulation of β -cell homeostasis; among Akt modulators, a central role is played by pleckstrin homology domain leucine-rich repeat protein phosphatase (PHLPP) family. Here, taking advantage of an in vitro model of chronic exposure to high glucose, we demonstrated that PHLPPs, particularly the second family member called PHLPP2, are implicated in the ability of pancreatic β cells to deal with glucose toxicity. We observed that INS-1 rat pancreatic β cell line maintained for 12–15 passages at high (30 mM) glucose concentrations (INS-1 HG) showed increased expression of PHLPP2 and PHLPP1 both at mRNA and protein level as compared to INS-1 maintained for the same number of passages in the presence of normal glucose levels (INS-1 NG). These changes were paralleled by decreased phosphorylation of Akt and by increased expression of apoptotic and autophagic markers. To investigate if PHLPPs had a casual role in the alteration of INS-1 homeostasis observed upon chronic exposure to high glucose concentrations, we took advantage of shRNA technology to specifically knock-down PHLPPs. We obtained proof-of-concept evidence that modulating PHLPPs expression may help to restore a healthy β cell mass, as the reduced expression of PHLPP2/1 was accompanied by a recovered balance between pro- and antiapoptotic factor levels. In conclusion, our data provide initial support for future studies aimed to identify pharmacological PHLPPs modulator to treat beta-cell survival impairment. They also contribute to shed some light on β -cell dysfunction, a complex and unsatisfactorily characterized phenomenon that has a central causative role in the pathogenesis of type 2 diabetes.